Analisis Peran Pengawas Pemeilihan Umum (Pemilu) Dalam Pemilihan Legislatif Menurut Undang-Undang Nomor 22 Tahun 2007 - Agussalem Agussalem (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2022)
Ideally, the General Election Supervisory Committee (Election) executes its supervisory authority. This thesis is titled Analysis of the Role of Election Supervisors in Legislative Elections Under Law No. 22 of 2007 Regarding General Election Organizers. This is an example of Empirical Legal Research. First, the Panwaslu of Baktiya Barat Sub-District plays an important role in the conduct of Baktiya Barat Sub-District legislative elections. The Panwaslu plays an active role in regulating candidates from different parties, however the Election Supervisory Committee for the West Baktiya Subdistrict has not maximized its supervisory capacity in terms of voter data updates. unable to accommodate This is evidenced by the fact that deceased individuals and fictional owners are still represented on the DPT for the election of members of the West Baktiya District Council. Second, the obstacles faced by election supervisors in legislative elections in Singgah Mata Village, West Baktiya District, namely internal constraints, specifically the lack of socialization from the KPPS chairman, lack of knowledge about election supervision, the number of KPPS members recruited not on the basis of ability but because of closeness, weak rules, and inadequate facilities and infrastructure. Among the external restraints are the public's ignorance of the significance of elections, the absence of oversight by the kpps, and Panwaslu's minimal authority